Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3144/expresspolymlett.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of binary polyvinylidene fluoride/barium titanate nanocomposites and their nanographite doped hybrids

Abstract: Abstract. Binary polyvinylidene fluoride/barium titanate (PVDF/BaTiO 3 ) and its nanographite (GN) doped ternary nanocomposites were fabricated using a simple solution casting process followed by compression molding. The dielectric behavior of such hybrids over a wide frequency range was studied. Additions of GN with contents close to the percolation threshold were found to be very effective to enhance dielectric permittivity of the PVDF/BaTiO 3 nanocomposites. In this regard, the electrical behavior of ternar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 18 publications
4
52
0
Order By: Relevance
“…It has been observed from Table (1). The dielectric loss factor increased with temperature for volume fraction (2, 4)%, due to chain motion of polymer is more effective due to glass transition temperature of the polymer, While the dielectric loss factor is low and remained more or less constant with increasing temperature for volume fraction (0,6)% because the orientation polarization due to chain motion of polymer can not keep phase with the rapidly oscillating electric field [28].…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed from Table (1). The dielectric loss factor increased with temperature for volume fraction (2, 4)%, due to chain motion of polymer is more effective due to glass transition temperature of the polymer, While the dielectric loss factor is low and remained more or less constant with increasing temperature for volume fraction (0,6)% because the orientation polarization due to chain motion of polymer can not keep phase with the rapidly oscillating electric field [28].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of filler materials enhances the conductivity as well as modifies the surface morphology. So incorporation of filler/dopant in PVDF, the materials chemical, physical and dielectric properties can be tailored [16][17][18]. Some work earlier demonstrated the increase in dielectric permittivity with addition of filler material [19,20].…”
Section: Introductionmentioning
confidence: 96%
“…The dielectric relaxation of the crystallites embedded into the polymer matrices was studied [15,16], and the principal role of the interface states on the border polymer-crystallites was established in defining the corresponding dielectric features. Barium titanate, a ferroelectric crystal with high dielectric strength, is widely used for this purpose [17][18][19][20]. The effects of barium titanate (BaTiO 3 ) nanoparticles on electric and mechanical properties are extensively studied, and it was found that the dielectric constant of nanocomposites significantly increases with the increasing BaTiO 3 concentration, whereas volume resistivity decreases continuously [21].…”
Section: Introductionmentioning
confidence: 99%